The Role of Tax Consultants in Improving Corporate Taxpayer Compliance in the Digital Era - Mela Novita Rizki; Irma Herliza Rizki (Outline Journal of Management and Accounting, 2024)
The digital era has brought about major changes in the tax administration system, creating challenges as well as opportunities for corporate taxpayers (WP Badan) to improve their compliance. This study aims to analyze the role of tax consultants in supporting the improvement of taxpayer compliance in the midst of digital transformation. The method used in this study involves a qualitative approach with descriptive analysis based on related literature and empirical studies. The results of the study indicate that tax consultants have significant contributions in several main aspects. First, tax consultants act as educational agents who help corporate taxpayers understand tax obligations and the latest regulations, including the use of digital technology such as e-Filing, e-Billing, and e-Invoices. Second, tax consultants provide technical assistance to minimize administrative errors and support the efficiency of tax reporting and payment. Third, tax planning prepared by tax consultants helps corporate taxpayers optimize tax obligations while taking advantage of available tax incentives. Digital transformation in the tax system strengthens the role of tax consultants by providing tools and technologies that simplify the process of tax reporting and management. However, this study also found several challenges faced by tax consultants, including limited resources and adaptation to rapid changes in technology and regulations.